Wage determinants in Spain (1980-2000) - José Aixalá; Carmen Pelet (Economia Aplicada, 2010)
This paper provides evidence about the nominal wage determinants in Spain during the period 1980-2000. We estimate a wage equation, using time series analysis applying an error correction mechanism. Our aim is to analyse the extent to which the evolution of wages is influenced by the unemployment, prices and productivity. The results reveal that the unemployment rate has no effect on the evolution of nominal wages. The variable that explains the evolution of nominal wages in the long term is prices, showing slightly inflationary behaviour. In the short term, wages are explained by their past values, reflecting a nominal inertia.